(untitled) (Herald of Journalism, 2016)
In this article the development of a Presidential form of government in the Republic of Kazakhstan is considered. The author emphasizes the right political choice, which was made at that time by Kazakhstan people – the choice of a President form of government. It was absolutely necessary, when there was the state independence establishment, when limiting concentration of the efforts of government and the people were needed, to realize radical political and economic reforms successfully, to get out of the crisis stage development. According to the author, the further development of a parliamentary and presidential form of government in Kazakhstan should be developed in the context of implementation of the grass-roots democracy and the democracy ideas, as well as the main directions of the political and state power reformation.